Doing "Business" in Papua New Guinea: The Social Embeddedness of Small Business Enterprises - Curry, George (International Council for Small Business, 2005)
Small-scale village businesses in PNG often become insolvent because the revenue, stock and cash normally earmarked for input costs are frequently redirected to the indigenous non-market economy. Many businesses are established primarily for facilitating gift exchange and enhancing the social status of their proprietors and investors, with the profit motive subordinated to these objectives. The important role of village enterprises in meeting indigenous socio-economic objectives means they are rarely profitable and must be subsidised with remittances from migrants or the income from cash cropping. These issues are explored in relation to wage labour, tradestores and cash cropping. A typology of enterprises is presented to illustrate how the characteristics of particular types of enterprises determine whether or not they will be able to accommodate the demands of the indigenous socio-economy while remaining solvent. Typically, businesses which require costly inputs and loanrepayments for their ongoing operations are less likely to be sustainable.